Iron Deficiency Anemia at Time of Vaccination Predicts Decreased Vaccine Response and Iron Supplementation at Time of Vaccination Increases Humoral Vaccine Response: A Birth Cohort Study and a Randomized Trial Follow-Up Study in Kenyan Infants - Stoffel, Nicole U.; Uyoga, Mary A.; Mutuku, Francis M.; Frost, Joe N.; Mwasi, Edith; Paganini, Daniela; van der Klis, Fiona R. M.; Malhotra, Indu J.; LaBeaud, A. Desiráe; Ricci, Cristian; Karanja, Simon; Drakesmith, Hal; et al. (Frontiers in Immunology, 2020)
Background: Iron deficiency may impair adaptive immunity and is common among African infants at time of vaccination. Whether iron deficiency impairs vaccine response and whether iron supplementation improves humoral vaccine response is uncertain. Methods: We performed two studies in southern coastal Kenya. In a birth cohort study, we followed infants to age 18mo and assessed whether anemia or iron deficiency at time of vaccination predicted vaccine response to three-valent oral polio, diphtheria-tetanus-whole cell pertussis-Haemophilus influenzae type b vaccine, ten-valent pneumococcal-conjugate vaccine and measles vaccine. Primary outcomes were anti-vaccine-IgG and seroconversion at age 24wk and 18mo. In a randomized trial cohort follow-up, children received a micronutrient powder (MNP) with 5mg iron daily or a MNP without iron for 4mo starting at age 7.5mo and received measles vaccine at 9 and 18mo; primary outcomes were anti-measles IgG, seroconversion and avidity at age 11.5mo and 4.5y. Findings: In the birth cohort study, 573 infants were enrolled and 303 completed the study. Controlling for sex, birthweight, anthropometric indices and maternal antibodies, hemoglobin at time of vaccination was the strongest positive predictor of: (A) anti-diphtheria and anti-pertussis-IgG at 24wk (p=0.0071, p=0.0339) and 18mo (p=0.0182, p=0.0360); (B) anti-pertussis filamentous hemagglutinin-IgG at 24wk (p=0.0423); and (C) anti-pneumococcus 19 IgG at 18mo (p=0.0129). Anemia and serum transferrin receptor at time of vaccination were the strongest predictors of seroconversion against diphtheria (p=0.0484, p=0.0439) and pneumococcus 19 at 18mo (p=0.0199, p=0.0327). In the randomized trial, 155 infants were recruited, 127 and 88 were assessed at age 11.5mo and 4.5y. Compared to infants that did not receive iron, those who received iron at time of vaccination had higher anti-measles-IgG (p=0.0415), seroconversion (p=0.0531) and IgG avidity (p=0.0425) at 11.5mo. Interpretation: In Kenyan infants, anemia and iron deficiency at time of vaccination predict decreased response to diphtheria, pertussis and pneumococcal vaccines. Primary response to measles vaccine may be increased by iron supplementation at time of vaccination. These findings argue that correction of iron deficiency during early infancy may improve vaccine response. Funding: Bill and Melinda Gates Foundation, DSM Nutrition, Philhuman Foundation, ETH Zurich